THE INFLUENCE OF CHILDREN'S DENTAL CARIES ON THE QUALITY OF LIFE IN STUDENTS IN SUB URBAN AND URBAN ENVIRONMENT - Ernie Thioritz; asridiana asridiana (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
Dental caries is a major problem of dental and oral health which most often occurs in children. If neglected, dental caries can cause pain, infection, premature tooth loss, and chewing disorders which can interfere with the consumption of an adequate diet. Furthermore, this will affect the child's growth and overall contribution to the environment. This can lead to weight loss, sleep disturbances, changes in behavior, and poor school performance, which will have an impact on the quality of life of the child. The purpose of this study was to determine the effect of dental caries in children on the quality of life of students in suburban and urban schools. This research is an analytic observational study with cross-sectional design and involved 257 samples with total sampling method. Dental caries was measured by the DMF-t index and children's quality of life was measured using the Child Perceptions Questionnaire (CPQ8-10). The results showed that in suburban schools, the number of respondents with "high" caries severity had the highest number, namely 47 people, while in urban schools, respondents with "moderate" caries severity level had the highest number, namely 42 people. Based on statistical tests using regression test, it was found that dental caries has a significant effect on the quality of life of students in both suburban and urban schools (p <0.05). It was concluded that dental caries has a significant effect on all quality of life domains. Key words: dental caries, quality of life, age 8-10 years.